2019
DOI: 10.1016/j.gene.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Type III collagen (COL3A1): Gene and protein structure, tissue distribution, and associated diseases

Abstract: Collagen alpha-1(III) chain, also known as the alpha 1 chain of type III collagen, is a protein that in humans is encoded by the COL3A1 gene. Three alpha 1 chains are required to form the type III collagen molecule which has a long triple-helical domain. Type III collagen, an extracellular matrix protein, is synthesized by cells as a pre-procollagen. It is found as a major structural component in hollow organs such as large blood vessels, uterus and bowel. Other functions of type III collagen include interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
184
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(198 citation statements)
references
References 168 publications
(255 reference statements)
9
184
0
5
Order By: Relevance
“…In addition, we found that knocking down the expression of COL3A1 by siRNA transfection will cause a decrease in the cytoplasmic COL3A1 protein level, thereby affecting cell proliferation, which is consistent with the published reports [30][31][32][33]; but the cells overexpress lnc-GULP-2:1 not only up-regulated the protein level of COL3A1, but also promoted the entry of COL3A1 protein into the nucleus, leading to the reduced level of cell proliferation. As for how this change of COL3A1 protein in the cytoplasm and nucleus affects the proliferation of granulosa cells, we have no clear experimental conclusions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that knocking down the expression of COL3A1 by siRNA transfection will cause a decrease in the cytoplasmic COL3A1 protein level, thereby affecting cell proliferation, which is consistent with the published reports [30][31][32][33]; but the cells overexpress lnc-GULP-2:1 not only up-regulated the protein level of COL3A1, but also promoted the entry of COL3A1 protein into the nucleus, leading to the reduced level of cell proliferation. As for how this change of COL3A1 protein in the cytoplasm and nucleus affects the proliferation of granulosa cells, we have no clear experimental conclusions.…”
Section: Discussionsupporting
confidence: 91%
“…COL3A1 gene encodes the pro-alpha1 chains of type III collagen, a brillar collagen that is found in extensible connective tissues, which is an important component of the extracellular matrix [29]. Studies have shown that several miRNAs can play a role in different diseases by down-regulating the expression of COL3A1 and inhibiting the proliferation of corresponding cells [30][31][32][33], indicating that the abnormal expression of COL3A1 plays an important role in the proliferation and development of various cells. There are also studies found that the expression of COL3A1 in cumulus cells is elevated under the stimulation of FSH [34], and FSH has the function of promoting granulosa cell proliferation [35,36], indicating that COL3A1 may affect the proliferation of granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen III is composed of three identical peptide chains encoded by the COL3A1 gene and is found throughout cortical bone [ 64 , 65 ]. A significantly higher level of COL3A1 mRNA expression has been observed in chemoresistant patients compared to those with a more favorable response to therapy [ 27 ].…”
Section: Ecm Components and Their Function In Osmentioning
confidence: 99%
“…The onset and severity of disease manifestation is highly variable even within families. Contributors include sexual dimorphism, with greater severity in males, and potent-ially other sources of genetic or environmental modification that remain to be defined (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%